META ANALISIS: PENGARUH MODEL PEMBELAJARAN TPS TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Arif Hidayatullah; Syamsuri Syamsuri; Maman Fathurrohman; Hepsi Nindiasari (LPPM Universitas Bina Bangsa, 2024)
This study investigates the impact of the Think-Pair-Share (TPS) model. TPS, which involves individual thinking stages, partner collaboration, and idea exchange, is implemented as an innovative strategy for understanding mathematics. The aim of this research is to evaluate the extent to which the implementation of the TPS model influences student learning. The research method involves Meta-Analysis, where 40 studies were obtained from the search, and 10 studies were selected based on inclusion and exclusion criteria. Meta-Analysis is used to determine the combined effect size by analyzing the selected studies that applied the TPS model. The anticipated results of this study are expected to provide insights into the effectiveness of the TPS learning model. Therefore, this research contributes to the development of teaching methods focused on achieving optimal learning outcomes. This study indicates that the Random Effect (RE) Model size from the implementation of the TPS learning method in improving mathematical problem-solving skills is 0.81, classified as a moderate effect